Development of a functional airway-on-a-chip by 3D cell printing. (30th October 2018) - Park, Ju Young; Ryu, Hyunryul; Lee, Byungjun; Ha, Dong-Heon; Ahn, Minjun; Kim, Suryong; Kim, Jae Yun; Jeon, Noo Li; Cho, Dong-Woo
Abstract: We used 3D cell printing to emulate an airway coupled with a naturally-derived blood vessel network in vitro . Decellularized extracellular matrix bioink derived from porcine tracheal mucosa (tmdECM) was used to encapsulate and print endothelial cells and fibroblasts within a designated polycarprolactone (PCL) frame. Providing a niche that emulates conditions in vivo, tmdECM gradually drives endothelial re-orientation, which leads to the formation of a lumen and blood vessel network. A fully-differentiated in vitro airway model was assembled with the printed vascular platform, and collectively reproduced a functional interface between the airway epithelium and the vascular network. The model presented respiratory symptoms including asthmatic airway inflammation and allergen-induced asthma exacerbation in physiological context. Because of the adaptable and automated nature of direct 3D cell printing, we expect that this will have relevance in vivo and high reproducibility for production of high-content platforms for preclinical trials in biomedical research.